Detection probability analysis of cooperative spectrum sensing with the Nthbest relay selection - Xiao-ge ZHANG; Shi-bing ZHANG; Gong-an QIU (Tongxin xuebao)
In the cognitive radio system,the optimal relay would be selected from the n available ones to obtain the best sensing performance.However,in actual systems,the secondary or even the more general Nthbest relay may be selected for various reasons.Therefore,the cooperative spectrum sensing based on the Nthbest relay selection was proposed.The closed-form expression of the detection probability was derived in Rayleigh fading channels.Numerical results show that the detection probability declines continuously even below the one of the arbitrary selection as N increases,and that the one based on the optimal or suboptimal selection increases obviously but the one based on the worst or near worst selection decreases slightly as n increases.